Effect of kinesiotherapy combined with Tai Chi on upper cross syndrome - zhou, Xiao (The Journal of the International Society of Chinese Health Practices, 2021)
The purpose of this study was to investigate the effect of kinesiotherapy combined with Tai Chi on upper chiasma syndrome. We will continue to deepen the existing correction model and explore effective methods that are helpful to solve the common modern supratidal syndrome. By referring to the typical movements that are helpful to shoulder, neck and upper limbs in Chen style Tai Chi and combining with the existing exercise therapy, a set of scientific, effective, simple and practical Tai Chi routines has been developed to balance the back muscles and improve the posture of patients. At the same time, observe the difference of the improvement results of the patients with supraciasmatic syndrome under the intervention of exercise therapy combined with Tai Chi compared with the intervention of exercise therapy alone. This study also has excellent application value: 1. Targeting correction training methods for patients with upper cross syndrome were given. 2. Provide effective and practical measures to prevent upper crossover syndrome for people who have been using electronic products for a long time. 3. To provide a new approach for the diagnosis and treatment of patients with suprachiasmatic syndrome or other related abnormal posture. Results: 1. Static neck and shoulder posture assessment: the head extension Angle (FHA) and round shoulder Angle (FSA) values of the exercise therapy + Tai Chi group were significantly decreased after the experiment (P <0. 05), and were significantly lower than those of the exercise therapy group (P <0. 05), while there was no significant change before and after the exercise therapy experiment. 2. The range of motion of cervical vertebrae: the flexion and rotation Angle of cervical vertebrae in the exercise therapy + Tai Chi group were significantly increased after the experiment (P <0. 05), which were significantly greater than that of the exercise therapy (P <0. 05), while the improvement before and after the exercise therapy experiment was not statistically significant. 3. VAS score: The VAS score of the exercise therapy + Tai Chi group was significantly decreased after the experiment (P<0. 05), and was significantly lower than that of the exercise therapy group (P<0. 05), while there was no significant change before and after the exercise therapy experiment. 4. NDI index: The NDI index of the exercise therapy + Tai Chi group was significantly decreased after the experiment (P<0. 05), and was significantly lower than that of the exercise therapy group (P <0. 05), while there was no significant change before and after the exercise therapy experiment. Conclusions: The two treatments have their own advantages. Tai Chi is designed to relieve pain, balance the neck and shoulders, and adjust breath. Exercise therapy is in the balance of muscle group strength, improve the activity function of cervical and thoracic vertebra, shoulder joint, correct posture is effective, so it can be used in combination, promote further rehabilitation of patients with this disease. The improvement of superior chiasmatic syndrome in the group of exercise therapy combined with Tai Chi was more significant than that in the group of exercise therapy alone. Prove that exercise therapy combined with tai chi to improve cross line in patients with muscle imbalances, adjust the head forward, wing shoulder, back, chest spine bending adverse symptoms improved, exercise therapy is a common way to solve the cross on the syndrome, the tai chi treatment combined with routine rehabilitation can provide new ideas for clinical correct spinal bad behavior, To further carry forward the motherland’s Tai Chi is worth popularizing.